Negative electrode material and preparation method thereof, negative electrode plate and lithium ion battery
By covering the conductive gel on the surface of nanometal particles, the three-dimensional porous structure is used to suppress volume expansion, the problem of nanometallic materials in lithium-ion batteries is solved, and the stability and electrochemical performance of the battery are improved.
Patent Information
- Application Number
- CN202411977766.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-30
AI Technical Summary
Nano-metallic materials, as the negative electrode material of lithium-ion batteries, will produce more than 300% of the volume expansion during the de-intercalation of lithium, resulting in material deformation, increase of internal impedance of the battery, and material powdering and falling off, seriously affecting the battery's cycling performance and specific capacity.
By covering the conductive gel on the surface of the nanometal particles, the three-dimensional porous structure of the conductive gel suppresses the volume expansion of the nanometal particles and promotes the transmission of electrons and ions, thereby improving the stability and electrochemical performance of the negative electrode material.
It effectively suppresses the volume expansion of nanometal particles, stabilizes the electrode structure, improves electrochemical performance, and extends the cycle life and specific capacity retention rate of the battery.
Smart Images

Figure CN119786571A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a negative electrode material and a preparation method thereof, a negative electrode plate and a lithium ion battery. Background Art
[0002] Lithium-ion batteries have the advantages of high operating voltage, high energy density, low cost, no memory, good safety, etc., and are widely used in digital products such as mobile phones, laptops, cameras, new energy vehicles, energy storage and other fields. At present, the mainstream negative electrode material of commercial lithium-ion batteries is graphite, but the theoretical specific capacity of graphite is limited and cannot meet the development needs of high power, miniaturization and high capacity of lithium-ion batteries. Therefore, the development of negative electrode materials with higher energy density is crucial to the development of high-capacity batteries.
[0003] Nanometal materials, such as tin-based materials and germanium-based materials, have the advantages of high specific capacity, moderate lithium deintercalation voltage, abundant natural reserves, low price, high safety and environmental protection, etc. They have attracted the attention of researchers and are regarded as one of the ideal negative electrode materials for the next generation of lithium-ion batteries. However, nanometal particles will produce more than 300% volume expansion during the lithium deintercalation process. The material deformation caused by this volume expansion will generate a large impedance inside the battery and cause the material to pulverize and fall off inside the battery, resulting in poor battery cycle performance and excessively fast specific capacity decay, which seriously affects the battery user experience. Summary of the invention
[0004] In view of the above problems existing in the prior art, the present invention provides a negative electrode material and a preparation method thereof, a negative electrode plate and a lithium ion battery to improve the volume expansion problem of nano-metal materials as negative electrodes during the cycle process.
[0005] To achieve the above-mentioned purpose and other related purposes, the first aspect of the present invention provides a negative electrode material, which includes nano-metal particles and a conductive gel, wherein the nano-metal particles include nano-tin particles and / or nano-germanium particles, and the conductive gel is coated on the surface of the nano-metal particles, and the conductive gel has a three-dimensional porous structure; wherein the mass content of the conductive gel in the negative electrode material is 29% to 58%, and the mass content of the nano-metal particles is 42% to 71%.
[0006] In one embodiment of the present invention, the mass content of the conductive gel in the negative electrode material is 34% to 50%, and the mass content of the nano metal particles is 50% to 66%.
[0007] In one embodiment of the present invention, the conductive gel is formed by a polymerization and cross-linking reaction of a conductive monomer and an organic acid, and the conductive monomer includes: at least one of aniline, aniline derivatives, thiophene, thiophene derivatives, pyrrole, and pyrrole derivatives; the organic acid includes at least one of phytic acid, citric acid, succinic acid, and tartaric acid.
[0008] In one embodiment of the present invention, in the C element spectrum of the XPS test of the negative electrode material, the position of 284.9 eV corresponds to a C=O bond, and the position of 286.7 eV corresponds to an O-C=O bond.
[0009] In one embodiment of the present invention, the peak intensity ratio of the C═O bond to the OC═O bond is (3.2-3.8):1.
[0010] In one embodiment of the present invention, the nano metal particles include primary particles and / or secondary particles formed by agglomeration of the primary particles, the particle size of the primary particles is 50 nm to 100 nm, and the particle size of the secondary particles is 200 nm to 400 nm.
[0011] A second aspect of the present invention provides a method for preparing a negative electrode material, the preparation method comprising the following steps:
[0012] Dispersing nano-metal particles in a solvent to obtain a first dispersion;
[0013] dispersing an oxidant in a solvent to obtain a second dispersion;
[0014] An organic acid and a conductive monomer are added to the first dispersion liquid, and after being evenly dispersed, a second dispersion liquid is added to obtain a conductive gel-coated nano-metal particle negative electrode material.
[0015] In one embodiment of the present invention, the added amount of the organic acid accounts for 6% to 60% of the mass of the nano-metal particles.
[0016] In one embodiment of the present invention, the added amount of the conductive monomer accounts for 10% to 50% of the mass of the nano-metal particles.
[0017] In one embodiment of the present invention, the added amount of the oxidant accounts for 0.15% to 10% of the mass of the nano-metal particles.
[0018] In one embodiment of the present invention, the conductive monomer includes at least one of aniline, aniline derivatives, thiophene, thiophene derivatives, pyrrole, and pyrrole derivatives.
[0019] In one embodiment of the present invention, the organic acid includes at least one of phytic acid, citric acid, succinic acid and tartaric acid.
[0020] In one embodiment of the present invention, the oxidant includes at least one of ammonium persulfate, hydrogen peroxide, ferric chloride, benzoyl peroxide, ammonium cerium sulfate, sodium persulfate, and cerium sulfate.
[0021] In one embodiment of the present invention, the solvent includes at least one of deionized water, methanol, ethanol, propanol, isopropanol, butanol, ethylene glycol, acetone, dimethylformamide, dimethyl sulfoxide, and ethyl acetate.
[0022] A third aspect of the present invention provides a negative electrode plate, comprising a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, wherein the negative electrode active material layer is composed of the above-mentioned negative electrode material.
[0023] A fourth aspect of the present invention provides a lithium-ion battery, comprising the negative electrode plate described above.
[0024] The negative electrode material of the present invention comprises nano-metal particles and conductive gel, wherein the conductive gel is coated on the surface of the nano-metal particles, and the conductive gel has a three-dimensional porous structure. The negative electrode material utilizes the three-dimensional porous structure of the conductive gel to suppress the volume expansion problem of the nano-metal particles and stabilize the electrode structure; at the same time, the three-dimensional porous structure and the nanostructure can promote the transmission of electrons and ions, thereby improving the stability and electrochemical performance of the metal nano-material negative electrode.
[0025] The present invention utilizes the polymerization and cross-linking reaction of conductive monomers and organic acids to in-situ coat the surface of nano-metal particles with conductive gel to form an in-situ composite negative electrode material of conductive gel-nano-metal material. The preparation method is simple, efficient and scalable. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other embodiments can be obtained based on these drawings without paying creative work.
[0027] Figure 1 A scanning electron microscope (SEM) image of the negative electrode material of the present invention;
[0028] Figure 2 A spectrum of the C element of the negative electrode material of the present invention measured by X-ray photoelectron spectroscopy (XPS) in one embodiment;
[0029] Figure 3 FIG. 1 is a flow chart of a method for preparing a negative electrode material according to an embodiment of the present invention. DETAILED DESCRIPTION
[0030] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the following embodiments and features in the embodiments can be combined with each other without conflict.
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0032] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:
[0033] As used herein, "plurality", "multiple", "multiple times", etc., unless otherwise specified, refer to a quantity greater than or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0034] Herein, "preferred", "better" and "more preferred" are only used to describe implementation methods or examples with better effects, and it should be understood that they do not constitute a limitation on the scope of protection of the present invention. If multiple "preferred" items appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "preferred" item is independent.
[0035] Herein, “further”, “furthermore”, “particularly”, etc. are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present invention.
[0036] In this article, when it comes to numerical ranges, unless otherwise specified, the distribution of optional values within the numerical range is considered continuous and includes the two numerical endpoints (i.e., the minimum value and the maximum value) of the numerical range, as well as every value between the two numerical endpoints. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined.
[0037] The present invention provides a negative electrode material and a preparation method thereof, a negative electrode plate and a lithium ion battery. By coating a conductive gel on the surface of nano metal particles, the three-dimensional porous structure of the conductive gel is utilized to inhibit the volume expansion of the nano metal particles, while promoting the transmission of electrons and ions, thereby improving the stability of the nano metal material structure and the electrochemical performance.
[0038] See also Figure 1 In the first aspect, the present invention provides a negative electrode material, which includes nano-metal particles and a conductive gel, wherein the conductive gel is coated on the surface of the nano-metal particles, and the conductive gel has a three-dimensional porous structure, and the nano-metal particles are distributed in the pores of the conductive gel. Wherein, the nano-metal particles can be any metal or alloy material that can be used as a negative electrode active material. As an example, the nano-metal particles include nano-tin particles and / or nano-germanium particles, that is, the nano-metal particles can only contain one of the above-mentioned materials, such as nano-metal particles are nano-tin particles, or nano-germanium particles; or they can also contain two of the above-mentioned materials, such as nano-metal particles are a combination of nano-tin particles and nano-germanium particles, and the ratio of nano-tin and nano-germanium particles in the composition is not limited, and can be mixed in any proportion. Those skilled in the art can choose according to actual needs. Nano-metal particles have the advantages of high specific capacity, moderate lithium insertion and extraction voltage, high safety and environmental protection, but there is a serious volume expansion during the lithium insertion and extraction process, and the conductive gel is coated on the surface of the nano-metal particles. The three-dimensional porous structure of the conductive gel can inhibit the volume expansion of the nano-metal particles during the cycle process, and promote the transmission of electrons and ions, thereby improving the electrochemical performance of the negative electrode. In addition, conductive gel is a polymer material that has the excellent properties of both gel and organic conductor. It has a high specific surface area and a three-dimensional continuous conductive network. Conductive gel can replace the binder and conductive agent in the electrode. At the same time, the three-dimensional porous structure of the conductive gel effectively enhances the electrical contact between metal particles, shortens the charge transfer path, and improves the transmission efficiency of electrons and ions, thereby improving the stability and electrochemical properties of the negative electrode of the nanometal material. Figure 1 This is the SEM image of the conductive gel-coated nano-tin particles (equipment model is TESCAN MIRA3 LMH). It can be seen that a three-dimensional porous microstructure and nanostructure are formed inside the composite material after being coated with the conductive gel. This structure provides additional buffer space for the volume expansion of the tin particles and significantly improves the structural stability of the tin negative electrode.
[0039] In order to make the negative electrode material meet the use requirements, the mass content of the conductive gel in the negative electrode material of the present invention is 29% to 58%, and the mass content of the nano-metal particles is 42% to 71%. Further, the mass content of the conductive gel in the negative electrode material is 34% to 50%, and the mass content of the nano-metal particles is 50% to 66%. Exemplarily, the mass content of the conductive gel in the negative electrode material is 34%, and the mass content of the nano-metal particles is 66%; or the mass content of the conductive gel in the negative electrode material is 45%, and the mass content of the nano-metal particles is 55%; or the mass content of the conductive gel is 50%, and the mass content of the nano-metal particles is 50%, etc.
[0040] In one embodiment, the conductive gel is formed by a cross-linking polymerization reaction of a conductive monomer (organic molecule) and an organic acid. The conductive monomer includes at least one of aniline, aniline derivatives, thiophene, thiophene derivatives, pyrrole, and pyrrole derivatives; the types of conductive monomers listed above can be used alone or in combination, as shown below: the conductive monomer is aniline, or thiophene, or a combination of thiophene and pyrrole, etc. Preferably, the conductive monomer is aniline and / or an aniline derivative, and aniline itself has good conductivity and no additional conductive material is required. The organic acid includes at least one of phytic acid, citric acid, succinic acid, and tartaric acid, for example, the organic acid is phytic acid, or citric acid, or a combination of succinic acid and tartaric acid, etc. In order to form a uniformly coated and high-quality conductive gel, the mass ratio of the conductive monomer to the organic acid is 1: (0.8-3.2), and for example, it can be 1: 0.8, or 1: 1.5, or 1: 2.0, or 1: 2.5, or 1: 3.2, and so on.
[0041] Since the conductive gel is formed by the polymerization and cross-linking of organic molecules, the conductive gel contains covalent bonds C=O and OC=O, which are formed when the conductive gel is formed through polymerization and cross-linking reactions. Since C=O and OC=O are covalent bonds, on the one hand, they can make the cohesion of the conductive gel stronger and the formed conductive gel more stable. On the other hand, it can also make the conductive gel more tightly and evenly coated on the surface of the nano-metal particles, thereby effectively inhibiting the volume expansion of the nano-metal particles, improving the structural stability of the composite material, and enhancing the electrochemical performance. The above covalent bonds can be measured by X-ray photoelectron spectrometer (XPS) on the negative electrode material test (XPS equipment model is Thermo Scientific, Escalab 250Xi), Figure 2 The XPS spectrum of the negative electrode material of Example 3 is shown. Figure 2 It can be seen that the position at about 284.9 eV in the XPS spectrum corresponds to a C=O bond, and the position at about 286.7 eV corresponds to an OC=O bond. The formation of the conductive gel can be confirmed by the XPS test. In addition, the inventors found in the study that when the peak intensity ratio of the C=O bond to the OC=O bond in the conductive gel is (3.2-3.8):1, the conductive gel can exhibit excellent performance. As an example, the peak intensity ratio of the C=O bond to the OC=O bond in the conductive gel can be 3.2:1, 3.5:1 or 3.8:1, etc. The peak intensity ratio can be adjusted by adjusting the ratio of the conductive monomer to the organic acid in the conductive gel.
[0042] In one embodiment, the nano-metal particles include primary particles and / or secondary particles formed by agglomeration of primary particles, wherein the particle size of the primary particles is 50nm to 100nm, for example, 50nm, 80nm or 100nm, and the particle size of the secondary particles is 200nm to 400nm, for example, 200nm, 300nm or 400nm. Small-sized active materials can effectively shorten the diffusion distance of lithium ions, so nano-metal particles are beneficial to achieve high-rate charge and discharge of electrode materials to a certain extent. However, nanoparticles are prone to agglomeration, so nano-metal particles may contain primary particles and secondary particles at the same time, or even all secondary particles. Nanoparticle agglomeration may lose the characteristics of nanoparticles, thereby affecting their cycle performance. The coating of conductive gel can make the nano-metal particles evenly dispersed in the three-dimensional network of conductive gel to alleviate the agglomeration and volume expansion problems of nanoparticles during charging and discharging.
[0043] See also Figure 3 The second aspect of the present invention provides a method for preparing the above-mentioned negative electrode material, the preparation method comprising the following steps:
[0044] S1, dispersing nano metal particles into a solvent to obtain a first dispersion;
[0045] S2, dispersing the oxidant into the solvent to obtain a second dispersion;
[0046] S3, adding organic acid and conductive monomer to the first dispersion, and then adding the second dispersion after uniform dispersion to obtain a conductive gel-coated nano-metal particle negative electrode material.
[0047] Specifically, the nano-metal particles in step S1 can be any metal material that can be used as a negative electrode active material. As an example, the nano-metal particles include nano-tin particles and / or nano-germanium particles, for example, the nano-metal particles are nano-tin particles, or nano-germanium particles; or a combination of nano-tin particles and nano-germanium particles. The solvent is used to disperse the nano-metal particles, and the solvent is selected from at least one of deionized water, methanol, ethanol, propanol, isopropanol, butanol, ethylene glycol, acetone, dimethylformamide, dimethyl sulfoxide, and ethyl acetate; further, the solvent is selected from at least one of deionized water, ethanol, isopropanol, and ethyl acetate, and further, the solvent is deionized water and / or ethanol. The dispersion treatment can select any technical means in the art that can evenly disperse the solid particles, such as ultrasonic treatment or high-speed stirring, etc. The amount of solvent added in this step increases with the increase in the mass of the nano-metal particles, as long as the nano-metal particles can be evenly dispersed. As an example, 0.2g to 5g of nanometal particles can be added with 1 to 50ml of solvent, for example, 0.2g of nanometal particles can be added with 1ml of solvent, or 2g of nanometal particles can be added with 10ml of solvent; or 5g of nanometal particles can be added with 50ml of solvent, and so on.
[0048] Step S2 is to evenly disperse the oxidant in the solvent to obtain an oxidant dispersion (second dispersion). The oxidant mainly plays a catalytic role in the polymerization process of the conductive gel. Therefore, the amount of the oxidant used in this step is related to the subsequent amount of conductive monomers and organic acids. The role of the solvent in this step is to disperse the oxidant, and the amount of solvent added is sufficient as long as the oxidant can be evenly dispersed. As an example, the mass of the oxidant in the second dispersion is 0.15-10% of the mass of the nanometal particles, for example, it can be 0.15%, 5%, 8% or 10%, etc.; the amount of solvent added is 2-20ml, for example, it can be 2ml, 10ml, 15ml or 20ml, etc.
[0049] In some embodiments, the oxidant includes at least one of ammonium persulfate, hydrogen peroxide, ferric chloride, benzoyl peroxide, ammonium cerium sulfate, sodium persulfate, and cerium sulfate. The oxidant can be selected from any one of the listed materials, such as ammonium persulfate, hydrogen peroxide, or ammonium cerium sulfate, etc. The oxidant can also be selected from any two or more combinations of the above-listed materials, such as a combination of ammonium persulfate and hydrogen peroxide, or a combination of benzoyl peroxide, ammonium cerium sulfate, and sodium persulfate, etc. It should be noted that when the oxidant is selected from two or more compositions, there is no restriction on the ratio between the components in the composition, and any proportion can be mixed.
[0050] The solvent in step S2 includes at least one of deionized water, methanol, ethanol, propanol, isopropanol, butanol, ethylene glycol, acetone, dimethylformamide, dimethyl sulfoxide, and ethyl acetate; further, the solvent is selected from at least one of deionized water, ethanol, isopropanol, and ethyl acetate, and further, the solvent is deionized water and / or ethanol. The solvent in this step may be the same as the solvent in step S1, or may be different, preferably the same. The dispersion treatment method in this step includes but is not limited to ultrasound and high-speed stirring.
[0051] It should be noted that there is no order between step S1 and step S2. Step S1 may be performed first and then S2, or S2 may be performed first and then step S1; or steps S1 and S2 may be performed simultaneously.
[0052] Step S3: adding the organic acid, the conductive monomer and the second dispersion liquid prepared in step S2 to the first dispersion liquid prepared in step S1, and causing the conductive monomer to undergo a polymerization and cross-linking reaction at room temperature to form a layer of conductive gel on the surface of the nano-metal particles; then removing the solvent to finally obtain a nano-metal negative electrode material coated with the conductive gel.
[0053] Among them, the organic acid plays a cross-linking role and is used for gel, and the organic acid includes at least one of phytic acid, citric acid, succinic acid, and tartaric acid; the conductive monomer is a monomer for forming a conductive gel, which can be selected from at least one of aniline, aniline derivatives, thiophene, thiophene derivatives, pyrrole, and pyrrole derivatives. Preferably, the conductive monomer includes aniline and / or aniline derivatives.
[0054] In step S3, the amount of organic acid added is 6% to 60% of the mass of the nano-metal particles; further, the amount of organic acid added is 10% to 50% of the mass of the nano-metal particles, for example, 20%, 30% or 40%, etc. The mass of conductive monomer added is 10% to 50% of the mass of the nano-metal particles; further, the mass of conductive monomer added is 10% to 40% of the mass of the nano-metal particles, for example, 10%, 20%, 30% or 40%, etc.
[0055] Preferably, when adding the organic acid, the conductive monomer and the second dispersion containing the oxidant to the first dispersion, the organic acid and the conductive monomer are added first, and after being dispersed evenly by ultrasound, the second dispersion is added. This is because the conductive monomer will rapidly undergo polymerization and cross-linking when it encounters the oxidant. The organic acid and the conductive monomer are first dispersed evenly, and then the oxidant is added, so that the conductive gel formed is more uniform.
[0056] The method for removing the solvent in step S3 is one or a combination of vacuum drying, spray drying, freeze drying, and filtration drying, preferably a combination of filtration drying and vacuum drying.
[0057] After step S3 is completed, a negative electrode material of conductive gel coated nanometal particles can be obtained. The conductive gel has the excellent properties of both gel and organic conductor. No additional conductive agent and binder are needed when preparing the negative electrode. The volume expansion of the nanometal is effectively suppressed, the electrode structure is stabilized, and the charge conduction efficiency is improved. It has a high reversible capacity and excellent charge and discharge kinetics.
[0058] A third aspect of the present invention provides a negative electrode plate, which includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, wherein the negative electrode active material layer is composed of the above-mentioned negative electrode material of the present invention.
[0059] Specifically, the negative electrode current collector can be selected from metal foil, such as copper foil or carbon-coated copper foil. The negative electrode current collector has a first surface and a second surface arranged opposite to each other along its thickness direction, and the negative electrode active material layer can be arranged on one of the first surface and the second surface, or on both surfaces at the same time. The negative electrode active material layer is formed by directly coating the above-mentioned negative electrode material of the present invention on the negative electrode current collector and drying it. In some embodiments, the single-sided thickness of the negative electrode active material layer is 7μm to 9μm, for example, 7μm, or 8μm or 9μm, etc.
[0060] A fourth aspect of the present invention provides a lithium ion battery, the lithium ion battery comprising the negative electrode sheet or negative electrode material of the present invention. The lithium ion battery can be a liquid lithium ion battery (the electrolyte is a non-aqueous electrolyte) or a solid lithium ion battery (the electrolyte is a solid electrolyte), which is not limited here.
[0061] Taking a liquid lithium-ion battery as an example, its structure is described in detail below: the lithium-ion battery includes a positive electrode plate, a negative electrode plate, a non-aqueous electrolyte and a separator, wherein the negative electrode plate is the negative electrode plate described above in the present invention, which is formed by directly coating the negative electrode material of the present invention on the negative electrode collector and drying it.
[0062] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector. The positive electrode current collector is, for example, aluminum foil or carbon-coated aluminum foil. The positive electrode active material layer can be disposed on the surface of one side of the positive electrode current collector, or on the surface of both sides. The positive electrode active material layer includes a positive electrode active material, a conductive agent, and a binder, wherein the positive electrode active material can select any positive electrode material suitable for lithium-ion batteries, that is, compounds that can reversibly embed and deintercalate lithium ions can be used. As an example, the positive electrode active material can be a ternary material, such as a nickel-cobalt-manganese ternary material (NCM), a nickel-cobalt-aluminum ternary material (NCA), etc., and the iron-lithium positive electrode material is, for example, lithium iron phosphate (LFP), lithium iron manganese phosphate (LMFP), etc., and can also be a traditional material such as lithium cobalt oxide and lithium manganese oxide. These materials can be used alone or in combination. The binder is, for example, any one or more of polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinyl ether, polymethyl methacrylate (PMMA), ethylene-propylene-diene terpolymer (EPDM), polyhexafluoropropylene, etc. The conductive agent includes, but is not limited to, at least one of conductive carbon black (SP), conductive graphite, carbon fiber, carbon nanotube, and graphene. Optionally, the conductive agent is conductive carbon black; or, a combination of carbon fiber and conductive carbon black; or, a combination of carbon nanotube and graphene, etc. The ratio of the positive electrode active material, the conductive agent, and the binder can refer to the conventional settings in the art.
[0063] The preparation process of the positive electrode sheet is exemplified as follows: first, the positive electrode active material, the conductive agent and the binder are mixed and stirred in a solvent such as N-methylpyrrolidone (NMP) in a certain ratio to form a positive electrode slurry, and then the positive electrode slurry is coated on the positive electrode collector. After drying, rolling, cutting and other processes, the positive electrode sheet is obtained.
[0064] The diaphragm is set between the positive electrode and the negative electrode to separate the positive electrode and the negative electrode to prevent short circuit inside the battery, and at the same time allow lithium ions to pass through and move between the positive and negative electrodes to realize the battery's charge and discharge process. The diaphragm can be made of porous materials such as polyethylene film (PE), polypropylene film (PP), glass fiber film or composite film. The thickness of the diaphragm is 9 to 18μm, the air permeability is 180s / 100mL to 380s / 100mL; the porosity is 30% to 50%.
[0065] The non-aqueous electrolyte plays a role in conducting lithium ions during the battery charging and discharging process. The non-aqueous electrolyte includes an organic solvent and a lithium salt, which can be selected from lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium perchlorate (LiClO4 ) lithium hexafluoroarsenate (LiAsF 6 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO 2 F 2 ), one or more of lithium difluorobis(oxalate)phosphate (LiDFOP) and lithium tetrafluorooxalate phosphate (LiTFOP). Further, the lithium salt is selected from lithium hexafluorophosphate or a combination of lithium hexafluorophosphate and other lithium salts with better comprehensive performance, such as a combination of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide. The organic solvent can be selected from one or more of fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), and ethyl propyl carbonate (EPC).
[0066] The non-aqueous electrolyte may also include functional additives such as fluoroethylene carbonate (FEC), propenyl-1,3-sultone (PST), tetravinylsilane (TVSI), vinylene carbonate (VC), diethylene sulfate (DTD), etc., which may be added according to actual production needs.
[0067] Battery assembly: Place the prepared positive electrode sheet, separator, and negative electrode sheet in sequence, with the separator placed between the positive and negative electrode sheets to isolate them, and obtain a bare cell by winding or stacking. Put the bare cell into the battery shell, and obtain a lithium-ion battery after assembly, injection, formation, and capacity division.
[0068] In other embodiments, the lithium-ion battery is a solid-state lithium-ion battery. The electrolyte of the solid-state lithium-ion battery is solid. Common solid-state electrolytes are oxide solid electrolytes, halide solid electrolytes, sulfide solid electrolytes, etc., which are not elaborated here. Those skilled in the art can make a selection according to actual production needs.
[0069] It should be noted that the structures not described in detail in the above lithium-ion battery can be configured with reference to the prior art and will not be described in detail here.
[0070] The lithium-ion battery of the present invention can be used in the form of a single cell, a battery module or a battery pack for electronic devices to power them. Electronic devices include but are not limited to mobile phones, tablets, laptops, electric toys, battery cars, new energy vehicles, ships, spacecraft, etc. Among them, electric toys can include fixed or mobile electric toys, for example, game consoles, electric car toys, electric ship toys and electric airplane toys, etc., and spacecraft can include airplanes, rockets, space shuttles and spacecraft, etc. New energy vehicles can be pure electric vehicles, hybrid vehicles or extended-range vehicles, etc.
[0071] The technical scheme of the present invention is described in detail below through several specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the examples are all commercially available.
[0072] Example 1
[0073] This embodiment provides a negative electrode material, which includes nano-tin particles and a conductive gel coated on the surface of the nano-tin particles, wherein the mass content of the conductive gel in the negative electrode material is 29.58%, and the mass content of the nano-tin is the remainder (70.42%).
[0074] The preparation process of the negative electrode material in this embodiment is as follows:
[0075] 1) taking 0.5 g of nano-tin particles and adding them into a sample bottle, adding 10 mL of deionized water, and performing ultrasonic treatment to obtain a first dispersion;
[0076] 2) adding 0.05 g of ammonium persulfate into 10 mL of deionized water and dispersing the mixture evenly to obtain a second dispersion;
[0077] 3) adding 0.16 g of phytic acid and 0.05 g of aniline to the first dispersion, performing ultrasonic treatment, and then adding the second dispersion. After adding the second dispersion containing the oxidant, the aniline is rapidly polymerized and cross-linked. Then, the solvent is removed to obtain a conductive gel-coated nano-tin composite material.
[0078] Example 2
[0079] The difference between this embodiment and embodiment 1 is that the mass content of the conductive gel in the negative electrode material is 34.21%.
[0080] In step 3) of the preparation method, 0.1 g of aniline is added.
[0081] Example 3
[0082] The difference between this embodiment and embodiment 1 is that the mass content of the conductive gel in the negative electrode material is 41.86%.
[0083] In step 3) of the preparation method, 0.2 g of aniline is added.
[0084] Example 4
[0085] The difference between this embodiment and embodiment 1 is that the mass content of the conductive gel in the negative electrode material is 45.05%.
[0086] In step 3) of the preparation method, 0.25 g of aniline is added.
[0087] Example 5
[0088] The difference between this embodiment and embodiment 1 is that the mass content of the conductive gel in the negative electrode material is 31.51%.
[0089] In step 3) of the preparation method, 0.03 g of phytic acid is added.
[0090] Example 6
[0091] The difference between this embodiment and embodiment 1 is that the mass content of the conductive gel in the negative electrode material is 33.33%.
[0092] In step 3) of the preparation method, 0.05 g of phytic acid is added.
[0093] Example 7
[0094] The difference between this embodiment and embodiment 1 is that the mass content of the conductive gel in the negative electrode material is 47.37%.
[0095] In step 3) of the preparation method, 0.25 g of phytic acid is added.
[0096] Example 8
[0097] The difference between this embodiment and embodiment 1 is that the mass content of the conductive gel in the negative electrode material is 50%.
[0098] In step 3) of the preparation method, 0.3 g of phytic acid is added.
[0099] Example 9
[0100] The difference between this embodiment and embodiment 1 is that the mass content of the conductive gel in the negative electrode material is 58%.
[0101] In step 3) of the preparation method, 0.3 g of phytic acid and 0.25 g of aniline are added.
[0102] Example 10
[0103] The difference between this embodiment and embodiment 3 is that: in step 3) of the preparation method, 0.16 g of phytic acid and 0.2 g of thiophene are added.
[0104] Embodiment 11
[0105] The difference between this embodiment and embodiment 3 is that: in step 3) of the preparation method, 0.16 g of phytic acid and 0.2 g of pyrrole are added.
[0106] Example 12
[0107] The difference between this embodiment and embodiment 3 is that: in step 3) of the preparation method, 0.16 g of citric acid and 0.2 g of aniline are added.
[0108] Embodiment 13
[0109] The difference between this embodiment and embodiment 3 is that: in step 3) of the preparation method, 0.16 g of succinic acid and 0.2 g of aniline are added.
[0110] Embodiment 14
[0111] The difference between this embodiment and embodiment 3 is that the nano-tin particles in step 1) of the preparation method are replaced with nano-germanium particles.
[0112] Comparative Example 1
[0113] The difference between this comparative example and Example 3 is that no oxidizing agent ammonium persulfate is added in the preparation method, that is, there is no step 2.
[0114] Comparative Example 2
[0115] The difference between this comparative example and Example 3 is that no organic acid (phytic acid) is added in step 3) of the preparation method.
[0116] Comparative Example 3
[0117] The difference between this comparative example and Example 3 is that in step 3) of the preparation method, no conductive monomer (aniline) is added.
[0118] In order to verify the performance of the negative electrode material of the present invention, the present invention respectively performs resistivity tests on the negative electrode sheets formed by the negative electrode materials of Examples 1-14 and Comparative Examples 1-3, and uses them in batteries to test their battery performance. The test results are shown in Table 1. The test method is as follows:
[0119] Battery Assembly:
[0120] Pole sheet preparation: The negative electrode materials of each embodiment and comparative example are uniformly coated on copper foil, dried in a vacuum drying oven at 110°C for 12 hours, taken out and cut into suitable sizes to serve as negative electrode sheets for batteries; the single-sided coating thickness of the negative electrode material is such that the thickness of the negative electrode active material layer formed after drying is 8 μm.
[0121] Diaphragm: Celgard 2400 polypropylene membrane is used as the diaphragm.
[0122] Electrolyte: Ethylene carbonate and diethyl carbonate with a volume ratio of 1:1 as solvent, LiPF 6 LiPF is a lithium salt in the electrolyte. 6 The concentration is 1.0 mol / L.
[0123] A button-type half-cell (CR 2025 type) is assembled with a metal lithium sheet as the counter electrode and the above-mentioned negative electrode sheet as the negative electrode.
[0124] (1) Conductive gel content test: Weigh part of the negative electrode material and record it as M 0 Place it in a thermogravimetric tester (NETZSCH STA449F3) and heat it from 25°C to 1000°C at a heating rate of 10°C / min in an oxygen atmosphere. After reaching 1000°C, keep it warm for 30 minutes. End the test and take it out and weigh it after it cools down to obtain M. 1 , then the conductive gel content W = (M 0 -M 1 ) / M 0 .
[0125] (2) Resistivity test: A four-probe resistivity tester is used to perform resistivity tests on negative electrode sheets made of various negative electrode materials.
[0126] (3) Electrochemical test equipment NEWARE CT-4008T, test voltage range 0.01 ~ 1.5V. -1 At the current density, the ratio of the first discharge capacity to the charge capacity is taken as the first charge and discharge efficiency (first coulomb efficiency) of the material. -1 The charge and discharge cycle test was carried out with the current, and the discharge capacity in grams in each cycle was recorded.
[0127] Capacity retention rate after 100 cycles = discharge capacity in grams after 100 cycles / discharge capacity in grams in the first cycle × 100%.
[0128] Table 1: Preparation parameters and properties of negative electrode materials of Examples 1-14 and Comparative Examples 1-3
[0129]
[0130]
[0131] It can be seen from Table 1 that the negative electrode materials of Examples 1 to 14 all form a three-dimensional conductive gel network, and the conductivity of the negative electrode sheet formed by the negative electrode material is significantly lower than the resistivity of Comparative Examples 1-3, indicating that the formation of the conductive gel improves the conductivity of the electrode; the negative electrode materials of Examples 1 to 14 are used in batteries, and the first coulomb efficiency and cycle capacity retention rate of the battery are improved compared with Comparative Examples 1-3, indicating that the formation of the conductive gel can inhibit the volume expansion of nano-metal particles and improve the stability of the electrode. Comparing the test results of Examples 1-14, it can be concluded that when the content of the conductive gel in the negative electrode material is 34% to 50%, the performance of the negative electrode material is better.
[0132] Comparing Examples 1-4, it can be seen that, under the premise of keeping other conditions unchanged, the amount of conductive monomer added is appropriately increased, and the content of conductive gel in the negative electrode material formed increases accordingly. The performance of the negative electrode material first increases and then decreases with the increase of the conductive gel content. This is because: the content of conductive gel in the negative electrode material increases, and the content of nano-metal particles decreases. Only when the ratio of conductive gel to nano-metal particles is moderate, the performance of the negative electrode material reaches the best.
[0133] Comparative Examples 5-8 show that, under the premise of keeping other conditions unchanged, the content of conductive gel in the negative electrode material formed increases with the appropriate increase in the amount of phytic acid added. The performance of the negative electrode material obtained is best when the amount of organic acid added accounts for 32% of the mass of the nano-metal particles and the amount of conductive monomer added accounts for 40% of the mass of the nano-metal particles.
[0134] By comparing Example 3 with Examples 10-14, it can be seen that different types of organic acids and different types of conductive monomers can form three-dimensional conductive gels on the surface of nanometal particles, thereby improving the stability and electrochemical performance of nanometal materials. Among them, when aniline is used as the conductive monomer and phytic acid is used as the organic acid, the negative electrode material of the conductive gel coated nanometal particles has the best performance.
[0135] By comparing Example 3 with Comparative Examples 1-3, it can be seen that when no oxidant is added, the organic acid and the conductive monomer cannot undergo a cross-linking reaction, thereby failing to form a three-dimensional conductive gel network on the surface of the nano-tin particles, resulting in reduced performance. In the absence of either an organic acid or a conductive monomer, the oxidant cannot play its due catalytic role. Only when the organic acid and the conductive monomer are present at the same time, the conductive gel will be formed by the catalysis of the oxidant.
[0136] The negative electrode material of the present invention comprises nano-metal particles coated with a conductive gel, and the three-dimensional porous structure of the conductive gel is used to suppress the volume expansion problem of the nano-metal particles and stabilize the electrode structure; at the same time, the three-dimensional porous structure and the nano-structure can promote the transmission of electrons and ions, thereby improving the stability and electrochemical performance of the negative electrode of the metal nano-material. In addition, the present invention utilizes the polymerization and cross-linking reaction of a conductive monomer and an organic acid to in-situ coat the surface of the nano-metal particles with a conductive gel, and the method is simple and easy to operate, and the negative electrode material has good conductivity, and no additional conductive agent needs to be added when preparing the electrode. Therefore, the present invention effectively overcomes some practical problems in the prior art and has a high utilization value and use significance.
[0137] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A negative electrode material, characterized in that: include: Nano metal particles, wherein the nano metal particles include nano tin particles and / or nano germanium particles; Conductive gel, coated on the surface of the nano metal particles, and the conductive gel has a three-dimensional porous structure; The mass content of the conductive gel in the negative electrode material is 29% to 58%, and the mass content of the nano metal particles is 42% to 71%.
2. The negative electrode material according to claim 1, characterized in that The mass content of the conductive gel in the negative electrode material is 34% to 50%, and the mass content of the nano metal particles is 50% to 66%.
3. The negative electrode material according to claim 1, characterized in that The conductive gel is formed by cross-linking a conductive monomer and an organic acid. The conductive monomer includes at least one of aniline, aniline derivatives, thiophene, thiophene derivatives, pyrrole, and pyrrole derivatives. The organic acid includes at least one of phytic acid, citric acid, succinic acid, and tartaric acid.
4. The negative electrode material according to claim 1, characterized in that In the C element spectrum of the XPS test of the negative electrode material, the position of 284.9 eV corresponds to a C=O bond, and the position of 286.7 eV corresponds to an O-C=O bond.
5. The negative electrode material according to claim 1, characterized in that The nano metal particles include primary particles and / or secondary particles formed by agglomeration of the primary particles. The particle size of the primary particles is 50 nm to 100 nm, and the particle size of the secondary particles is 200 nm to 400 nm.
6. A method for preparing the negative electrode material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Dispersing nano-metal particles in a solvent to obtain a first dispersion; dispersing an oxidant in a solvent to obtain a second dispersion; An organic acid and a conductive monomer are added to the first dispersion liquid, and after being evenly dispersed, a second dispersion liquid is added to obtain a conductive gel-coated nano-metal particle negative electrode material.
7. The preparation method according to claim 6, characterized in that: Include one or more of the following: The amount of the organic acid added is 6% to 60% of the mass of the nano metal particles; The added amount of the conductive monomer accounts for 10% to 50% of the mass of the nano metal particles; The added amount of the oxidant accounts for 0.15% to 10% of the mass of the nano metal particles.
8. The preparation method according to claim 6, characterized in that: Include one or more of the following: The conductive monomer includes at least one of aniline, aniline derivatives, thiophene, thiophene derivatives, pyrrole, and pyrrole derivatives; The organic acid comprises at least one of phytic acid, citric acid, succinic acid and tartaric acid; The oxidant comprises at least one of ammonium persulfate, hydrogen peroxide, ferric chloride, benzoyl peroxide, ammonium cerium sulfate, sodium persulfate, and cerium sulfate; The solvent includes at least one of deionized water, methanol, ethanol, propanol, isopropanol, butanol, ethylene glycol, acetone, dimethylformamide, dimethyl sulfoxide, and ethyl acetate.
9. A negative electrode plate, characterized in that: The invention comprises a negative electrode current collector and a negative electrode active material layer arranged on the negative electrode current collector, wherein the negative electrode active material layer is composed of the negative electrode material according to any one of claims 1 to 5.
10. A lithium ion battery, characterized in that: Including the negative electrode sheet as described in claim 9.
Citation Information
Patent Citations
Preparation method of metal nano-particles coated with graphene modified conductive polymer gel
CN106229514A
Preparation method of polyaniline gel coated tin-copper nanotube composite
CN106410159A
Lithium ion battery anode composite material and preparation methods thereof
CN109786707A
Nano tin-silicon composite negative electrode material and preparation method and application thereof
CN111048763A
Gel type silicon-based negative electrode material, preparation method and application thereof, and lithium ion battery
CN114430041A
Cited By
Conductive fiber film electrode
TWI940377B